Effect of demulsification on anionic surfactantstabilized oil-in-water emulsion using graphene oxide - Zukmi, Nur Arifah Nabila (2018)
Emulsion problem in oil and gas industry is a serious problem and need to be overcome. This is because formation of emulsion can cause problems such as production loss, pressure loss and tripping in production facilities. One of the best way to separate emulsion is by using demulsifier. Graphene Oxide (GO), due to its amphiphilic behavior had received attention as potential demulsifying agent. Synthesis of GO was done by using Hummer’s modified method and was characterized by using X-Ray Diffractometer (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). Result shows that GO was successfully obtained when XRD result shows peak of 2 = 10.02 and FTIR result shows the presence of functional groups such as –OH, C=O and C-O. Synthetic oil using n-heptane and toluene was used to provide oil medium while SDS, an anionic surfactant was used to create emulsion. Performance of GO to break the emulsion was tested at different water cut of 1:1, 1:2, 1:3 and 1:4 and result shows that GO helps in increasing rate of separation with different water cut having their own optimum dosage of GO needed. GO was also tested at different pH condition and result shows that GO can perform well in acidic and neutral condition as had been predicted. On the contrary, although in alkali condition GO was predicted to be not effective, result had shown good reparation rate. However, result at alkali condition was believed to be affected by decrease in interfacial tension between water and synthetic crude caused by presence of SDS surfactant.